2023
DOI: 10.3390/children10050779
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Additional Granola in Children’s Breakfast on Nutritional Balance, Sleep and Defecation: An Open-Label Randomized Cross-Over Trial

Abstract: The contribution of breakfast to daily nutrient intake is low, particularly among children, at only about 20%, and it is difficult to determine whether children are receiving adequate nutrients at breakfast. Although alterations in breakfast content are considered to affect lifestyle habits such as sleep and defecation, there have been few intervention studies in children. The relationship between nutritional balance, dietary intake, and lifestyle habits in children remains unclear. We conducted an interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The primary outcome was the amount of intestinal IgA, with gut microbiome and metabolome composition, and defecation data we could collect (frequency, amount, consistency, color, odor, feeling of incomplete evacuation, and abstinence) secondary outcomes. At each time point, subjects were asked to collect fecal samples; (1) prior to starting cereal intake, (2) 2 weeks after starting cereal intake, and (3) 4 weeks after intake. Collected fecal samples were preserved at −20°C until processing.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary outcome was the amount of intestinal IgA, with gut microbiome and metabolome composition, and defecation data we could collect (frequency, amount, consistency, color, odor, feeling of incomplete evacuation, and abstinence) secondary outcomes. At each time point, subjects were asked to collect fecal samples; (1) prior to starting cereal intake, (2) 2 weeks after starting cereal intake, and (3) 4 weeks after intake. Collected fecal samples were preserved at −20°C until processing.…”
Section: Methodsmentioning
confidence: 99%
“…Cereals are commonly consumed worldwide, with the increasing westernization of diets in Corn flakes (CF), which consists almost entirely of cornderived dietary fiber, while FG contains a mix of dietary fibers from oats, rye, dried fruits, and nuts. We have previously reported that FG consumption for breakfast enhances bowel movements in adult women and elementary school children (1,5). It also leads to reduced blood pressure, urinary toxin indoxyl sulfate, and improved stool characteristics for hemodialysis patients (6).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation